THE ROLE OF CIVIL SOCIETY IN CREATING INCLUSIVE CITIES - Vinci, Amanda Carolina da Silva (Seven Editora, 2025)
The purpose of this article is to analyze the relationship between the right to the city and housing policies in São Paulo, focusing on occupations promoted by housing movements in central areas. An interdisciplinary approach was adopted, combining normative analysis of urban and housing legislation with a bibliographical review of academic studies and official documents on social mobilization and participatory governance. The results showed occupations respond to a structural housing deficit resulting from historical processes of marginalization; that instruments of participatory democracy play a decisive role in the formulation and continuity of inclusive policies; and that the reuse of empty urban spaces for social housing strengthens the dialogue between civil society, public authorities and private initiative. In the end, we highlight the need to institutionalize participatory channels to ensure the continuity of these policies and propose investigating their applicability in other Brazilian metropolises. DOI: https://doi.org/10.56238/sevened2025.036-115